Interleukin 8 in children with obstructive sleep apnea before and after adenotonsillectomy - Nourhan I. Abdelmonem; Mohammed T. El Tabbakh; Alaa M. Farid; Mohamed S. Rashwan (The Egyptian Journal of Otolaryngology, 2023)
Abstract Objective To assess serum interleukin 8 (IL-8) levels after adenotonsillectomy in children with symptoms suggestive for OSA. Study design Prospective interventional study. Settings The study was carried out on 30 children with OSA attending ENT clinic of Suez Canal University Hospital. Methods Including, children with sleep-related chronic intermittent hypoxia (CIH) and OSA symptoms performed an elective adenotonsillectomy, and aged (3–12 years). Excluding, children with acute tonsillitis, cardiorespiratory, craniofacial, or diseases affecting IL-8 level as cystic fibrosis, COVID-19 patients, and hepatitis C, taking drugs affecting IL-8 level as benzodiazepines or glutamine supplementation. Children were subjected to full history, clinical examination and laboratory investigations. Nocturnal pulse oximetry (ChoiceMMed) was performed (48–72 h preoperative and 3–4 weeks postoperative) used to determine the number of 4% dips in saturation from baseline, and the nadir saturation (nSAT). IL-8 was measured 1 month pre-operative and 1 month post-operative by flow cytometry using the Human Inflammatory Cytometric Bead Array kit. Results The mean preoperative IL-8 (237.55 p/ml) and oxygen desaturation index (7.77%)cwere statistically significantly higher than mean postoperative IL-8 (207.98 p/ml) and oxygen desaturation index (2.90). The mean pre-operative SpO2 is 98.27 ranged (96.00–100.0%), while the mean postoperative SpO2 is 98.77 ranged (97.00–100.0%), with no statistically significant difference between them (p = 0.069). Preoperative IL-8 (p/ml), postoperative IL-8 (p/ml), and preoperative SpO2 (%) were found to be negatively correlated with IL-8 change. Conclusion IL-8 level significantly decreased after adenotonsillectomy in children with symptoms suggestive for OSA.